Anti-inflammatory effects of purple sweet potato anthocyanin extract in DSS-induced colitis: modulation of commensal bacteria and attenuated bacterial intestinal infection. Issue 22 (26th October 2021) - Mu, Jingjing; Xu, Jingwen; Wang, Linlin; Chen, Caifa; Chen, Ping
Abstract : Purple sweet potato anthocyanin extract had effective abilities in inhibiting the increase of pathogens to maintain gut homeostasis during DSS-induced chronic colitis. Abstract : Purple sweet potato anthocyanins have been acknowledged for their beneficial effects on human inflammatory bowel diseases (IBD). Although the ability of anthocyanins in modulating the gut microbiota has been reported, the relationship between the bacteria modulated by anthocyanins and intestinal inflammation has not been fully elucidated. We aimed to ascertain whether the purple sweet potato anthocyanin extract (PSPAE) modulation of gut microbiota in the dextran sodium sulphate (DSS) induced chronic colitis mouse model could result in the maintenance of intestinal homeostasis and protection against bacterial intestinal inflammation. Chronic colitis was induced by adding DSS in drinking water while administering the mice with PSPAE via gavage (20 mg kg −1 ). Effects on colon tissue damage, gut microbiota composition, tight junction protein, and cytokines were evaluated. PSPAE prevented the loss of Bifidobacterium and Lactobacillus and inhibited the increase of Gammaproteobacteria and Helicobacter upon DSS treatment. The non-pathogenic-dependent and pathogenic-dependent microenvironments were established upon treatment with broad-spectrum antibiotics. Both PSPAE treatment and non-pathogenic treatments modified the colonic expression of mouse tight junction proteins and maintained the architecture of the colon. However, the non-pathogenic treatment could not attenuate intestinal inflammation. Moreover, the pathogenic-dependent dysbiosis was exacerbated because of the increasing colonization of pathogens such as Helicobacter . The PSPAE exerted the modulation of gut microbiota to maintain the gut microbiome homeostasis in DSS-induced chronic colitis mice, which may help to propose a new treatment that combines efficacy and reduction of the possibility of bacterial intestinal infection.